EFEKTIVITAS MEDIA PERMATA KITA TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG POLA ASUH MAKAN PADA BALITA - Rusyaida Syarifa; Novelasari Novelasari; Nindy Audia Nadira; Widdefrita Widdefrita; Neni Fitra Hayati (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
Based on mass weighing in August 2021, 40 out of 85 toddlers in Nagari Sirukam Jorong Ganting, Solok District, West Sumatera Province, were identified as having nutritional problems, including stunting, undernutrition, risk of overnutrition, and obesity. This study aimed to determine the effectiveness of PERMATA KITA Media (snakes and ladders game and smart cards) on the score of knowledge and attitudes of mothers about feeding parenting in toddlers in Jorong Ganting, Nagari Sirukam. This research is mixed method research by using two approaches, namely quantitative, using a quasi-experiment with a one-group pre-test post-test design, and qualitative, using exploratory case studies. This research was conducted from September 2022 to June 2023. The population in this study were mothers of toddlers, with a total sampling technique of 87 people. Informants in qualitative research are mothers of toddlers, posyandu cadres, linguists, design experts, nutrition program holders, and Sirukam Health Center health promotion. Data were collected using questionnaires and interview guidelines. Data processing was carried out using the SPSS program in univariate and bivariate with the Wilcoxon test. Based on the results of the study, there was an increase in the average value of knowledge of mothers of toddlers before and after the intervention by 13.96 and attitudes by 3.51. The results showed that there was an effectiveness of PERMATA KITA media on knowledge (p=0.0001). The study concluded that PERMATA KITA media is effective in increasing the score of knowledge and attitudes of mothers about eating parenting in toddlers in Jorong Ganting, Nagari Sirukam.